THE EFFECTS OF ADDITIVE ON THE IMPACT ABSORPTION CAPABILITY OF MAGNETORHEOLOGICAL ELASTOMER (Jurnal Teknologi (Sciences & Engineering), 2023)
Magnetorheological elastomer (MRE) is a smart material whose its damping and stiffness characteristics change when exposed to a magnetic field. MRE usually contains rubber and ferrous particles. Other materials such as additives, can improve physical properties of MRE during cyclic loading. However, limited research has been conducted into the effect of incorporating these additives on MRE performance when subjected to impact loading. Additives can change the MRE’s structure such as stiffness and enhance its damping properties, especially its impact absorption capabilities. This study focuses on the force-displacement characteristics of additives and their relationships with MRE containing additives in impact absorption applications. This study uses ferrite, zinc, aluminum, and copper as additives in MREs fabrication and subjects the MREs to a drop impact test at varying applied currents of 0, 0.5, 1.0, 1.5, and 2.0 ampere. The experimental results show that the MRE containing ferrite has the highest average impact absorption capability of 2.24 Nm, followed by zinc, aluminum, and copper.